2021
DOI: 10.1177/14759217211008620
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Lamb wave propagation method for nondestructive monitoring of matrix cracking in laminated composites

Abstract: The estimation of the damping coefficient may help to improve the damage detection in composite materials. The purpose of this study was to develop the simulated Lamb wave propagation method for nondestructive monitoring of matrix cracking in laminated composites via the accurate estimation of their damping coefficient. Cross-ply composite specimens with different crack densities were fabricated and tested by the Lamb wave propagation technique. The phase velocity of the Lamb wave and the damping coefficient o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…At the cost of significant computational power requirements, numerical methods allow for complex real case scenario simulation. Recent advances covers in particular: Guided waves scattering on impact damage of composite structures [ 43 , 47 ] or delaminations [ 48 ]; Transmission of guided waves across partially-closed cracks [ 49 ]; Wave damage interaction coefficients for lightweight structures [ 10 ]; Damage of reinforced concrete beams [ 50 ]; Looseness of joint structures in cylindrical waveguides [ 51 ]; Matrix cracking in laminated composites [ 52 ]. …”
Section: Materials and Methodsmentioning
confidence: 99%
“…At the cost of significant computational power requirements, numerical methods allow for complex real case scenario simulation. Recent advances covers in particular: Guided waves scattering on impact damage of composite structures [ 43 , 47 ] or delaminations [ 48 ]; Transmission of guided waves across partially-closed cracks [ 49 ]; Wave damage interaction coefficients for lightweight structures [ 10 ]; Damage of reinforced concrete beams [ 50 ]; Looseness of joint structures in cylindrical waveguides [ 51 ]; Matrix cracking in laminated composites [ 52 ]. …”
Section: Materials and Methodsmentioning
confidence: 99%
“…Lamb waves are typical ultrasonic guided waves propagating in plate-like structures and are capable of propagating long distances. It has been confirmed that Lamb waves are sensitive to both surface and internal defects, such as crack, 1 corrosion, 2 matrix cracking, 3 and delamination. 4 Lamb wave-based structural health monitoring (SHM) and nondestructive testing (NDT) methods are efficient because these methods can monitor or detect the area of the whole Lamb wave propagation path.…”
Section: Introductionmentioning
confidence: 91%
“…Many researchers have used finite element (FE) simulations to investigate the wave propagation problems. [34][35][36][37][38][39][40][41][42] For example, Alleyne and Cawley 35 assessed the interaction of the Lamb waves and defects in plate-like structures using FE simulations. They showed that different parameters affect the sensitivity of Lamb waves to defects, including the geometry of the plate, wave mode, wave frequency-thickness, and the type of the notch defect.…”
Section: Introductionmentioning
confidence: 99%
“…The finite element method (FEM) is the most stable numerical solution technique to study the characteristics of wave propagation in different structures. Many researchers have used finite element (FE) simulations to investigate the wave propagation problems 34–42 . For example, Alleyne and Cawley 35 assessed the interaction of the Lamb waves and defects in plate‐like structures using FE simulations.…”
Section: Introductionmentioning
confidence: 99%